(untitled) (The New Uzbekistan Journal of Medicine, 2025)
This study presents a comparative analysis of morphological changes in the spleen in animals of the same age with chronic kidney failure (CKF). The relevance of the research is due to the high prevalence and increasing incidence of kidney diseases worldwide, as well as their serious medical, social, and economic consequences. CKF develops as a result of various pathological processes, including diabetes mellitus, arterial hypertension, chronic glomerulonephritis, and congenital kidney anomalies. As the disease progresses, there is a significant disruption of homeostasis, accompanied by disturbances in electrolyte and protein metabolism, as well as the accumulation of metabolic by-products. In this regard, studying the morphological changes in the spleen in CKF represents an important research direction. This study examines the main mechanisms of pathological changes occurring in the spleen in CKF, their relationship with kidney dysfunction, and possible ways to correct the identified disorders.